Adaptive functioning index (AFI). - Marlett, Nancy J. (The Vocational and Rehabilitation Research Institute (VRRI), 1971)
The Adaptive Functioning Index (AFI) is a training device which uses assessment as the starting point in rehabilitation and as the means of evaluating and reinforcing change. It is designed for use with adolescents and adults who are generally characterized by a degree of inadequate intellectual functioning, and/or a history of institutionalization or social disadvantage, which prevents social independence. The index consists of three separate, but compatible, program units: Social Education, Vocational, and Residential.